The efforts of the writer Al_Tanukhi the history of public aspects in Baghdad 327 _ 384 AH / 938 _994 AD - عباس, رندة (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
Despite the efforts of the Abbasid historians (during the Buyid rule 334 – 447 AH / 946 – 1055 AD) to chronicle the events of that era, with the progress of codification methods in governance, public and local history, biography, and translations, but they wrote down the prominent political events, and under the supervision of the rulers While literary sources were far from the rulers control and were preoccupied with the history of the daily life of the common people, they recorded important events in political, social, economic and intellectual affairs Among these writers was Tankhi in his book The talk of the lecture, which was distinguished in its accurate history of the daily life of the public